(untitled) (Strathmore Law Journal, 2021)
The COVID-19 pandemic has left a massive amount of disease, death, fear and despair in its stride, and will continue to seriously trouble the world even in its wake. To be sure, Africa has not been spared any of these maladies. In the result, the pandemic has posed a formidable threat to the enjoyment of human rights around the world. More specifically, as is widely recognised, the pandemic (and many of the measures taken to end it) have seriously threatened or harmed the enjoyment by billions of people across the world, the continent included, of the human rights to health, life, education, food, shelter, work, freedom of movement, liberty, and freedom of assembly. Less obvious to many is the fact that the pandemic (and the dominant responses to it) can also constitute serious harm to the enjoyment of the rights to development and democracy, and to freedom from discrimination and gender-based violence. Even more troubling is the fact that these dangers and impacts tend to be exacerbated in the Global South to which Africa belongs geo-politically and identity-wise, and in relation to the poor and the racially marginalised everywhere.